2020
DOI: 10.1101/2020.09.10.20191486
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization and Phase 1 Trial of a B Cell Activating Anti-CD73 Antibody for the Immunotherapy of COVID-19

Abstract: COVID-19 is a global pandemic that has resulted in over 800,000 deaths. Robust humoral anti-viral immune responses have the potential to generate a diverse set of neutralizing antibodies to eliminate viruses and protect against re-infection, transmission, and the evolution of mutations that escape targeted therapeutics. CD73 is present on the majority of human B cells and a subset of T cells where it plays a role in lymphocyte activation and migration. CD73 also functions as an ectoenzyme that converts AMP in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…CD73 was originally characterized as a costimulatory molecule for T cells, but our previously reported results presented demonstrated that mupadolimab predominantly activates CD73 POS B cells. [17] CD73 is most highly expressed on human IgD POS IgM DIM/NEG naïve B cells, and CD27 POS memory B cells expressing IgG or IgA. [11] Mupadolimab induces the expression of CD69, an activation marker that negatively regulates S1PR1 function, resulting in the prolonged retention of activated B cells in lymphoid organs and thymus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CD73 was originally characterized as a costimulatory molecule for T cells, but our previously reported results presented demonstrated that mupadolimab predominantly activates CD73 POS B cells. [17] CD73 is most highly expressed on human IgD POS IgM DIM/NEG naïve B cells, and CD27 POS memory B cells expressing IgG or IgA. [11] Mupadolimab induces the expression of CD69, an activation marker that negatively regulates S1PR1 function, resulting in the prolonged retention of activated B cells in lymphoid organs and thymus.…”
Section: Discussionmentioning
confidence: 99%
“…Serum concentrations of mupadolimab achieved levels exceeding 1 µg/ml for greater than 24 hours for doses of 1 mg/kg and higher; concentrations known to activate B cells in vitro. [17] IgG titers were sustained without decrement up to 6 months after POS (Figure 2C). Antibody levels reached higher titers compared to convalescent sera from recovered patients (convalescent sera collected at 4-6 weeks POS, no comorbidities, and median age of 40) (Figure 2A-B, 2D-E).…”
Section: Immune Responses In Mupadolimab Treated Covid-19 Patientsmentioning
confidence: 92%
See 1 more Smart Citation
“…Many similar agents are in early-stage discovery and preclinical development [95,[97][98][99][100][101][102]. Somewhat surprisingly, some anti-CD73 antibodies are already being tested for coronavirus disease 2019 (COVID-19) therapy [103,104], despite evidence of clinical benefits of CD73 and adenosine in lung injury [105], and benefit of adenosine in pneumonia associated with COVID-19 [106]. CD73 activity on immune cells versus other types of cells (endothelial, epithelial) need to be carefully considered to advance safe and effective treatments for COVID-19.…”
Section: Development Of Cd73 Inhibitors and Other Tools To Support Further Researchmentioning
confidence: 99%
“…Importantly, these findings have translational implications for human liver diseases, as well as anti-CD73 antibodies and inhibitors, which currently are undergoing clinical development for cancer 26 and COVID-19 immunotherapy. 27 …”
mentioning
confidence: 99%